2017
DOI: 10.1016/j.seppur.2017.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Electricity production from human urine in ceramic microbial fuel cells with alternative non-fluorinated polymer binders for cathode construction

Abstract: Urine-fed ceramic MFCs for bioenergy production and urine treatment.  Alternative non-fluorinated polymers as binders in ceramic MFCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…A previous study investigating PTFE alternatives has shown, with a different MFC design (i.e. ceramic membrane), that chitosan was a good alternative [ 47 ]. The MFCs mounted with chitosan based cathodes were producing 40% less power (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study investigating PTFE alternatives has shown, with a different MFC design (i.e. ceramic membrane), that chitosan was a good alternative [ 47 ]. The MFCs mounted with chitosan based cathodes were producing 40% less power (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The MFCs mounted with chitosan based cathodes were producing 40% less power (i.e. maximum power) than the PTFE control whilst using only 2.5% of binder [ 47 ]. Compared to these results, the PVA-10 cathodes seem to be a good alternative since they were producing 85% of the maximum power produced by the control ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was first demonstrated in 2012 that MFCs generated electricity from diluted urine, and this electricity could be used to power cell phones ( Ieropoulos et al, 2013 ). Subsequently, research on enhanced MFC systems aims to improve the cathode structure, provide for more efficient nutrients/energy recovery, and support pathogen inactivation ( Ieropoulos et al, 2017 , Merino-Jimenez et al, 2017 , Salar-Garcia et al, 2017 , Zang et al, 2012 ). MECs are normally associated with hydrogen production and nutrient recovery ( Kuntke et al, 2014 ), and researchers are focusing on efficient nutrient recovery by controlling the load ratio, changing the electric current conditions, and developing electrodes ( Dbira et al, 2015 ; Rodriguez Arredondo et al, 2017 ; Yuan and Kim, 2017 ).…”
Section: Sanitation Activities In Scientific Researchmentioning
confidence: 99%
“…Urine is an excellent raw material for MFC systems for real applications 26 . In addition to treating urine with MFC, the results of recent studies are promising for the direct recovery of bioelectricity from urine 27,28 . A system of MFCs inoculated with activated sludge and fueled with human urine has been practically applied in the lighting systems 29 .…”
Section: Introductionmentioning
confidence: 99%